Integrating and ranking sustainability criteria for housing - Abdul-Rahman, H.; Wang, C.; Wood, Lincoln; Ebrahimi, M. (2015)
Numerous researchers have determined building sustainability criteria relating to environmental performance, but the other two sustainability components – economic and social performance – have not been taken into consideration in an integrated and hierarchical manner. Existing sustainability assessment methods generally ignore economic and social aspects, and sustainable criteria are not prioritised for facilitating decision making. This paper reports how a fuzzy analytic hierarchical process tool was employed to prioritise sustainability criteria for residential buildings for environmental, economic and social performance in an integrated manner. A structured expert-based development process, comprising 17 building practitioners and eight academics from 16 nations was conducted globally. A fuzzy weighted hierarchy for all three aspects of sustainability in residential buildings was developed at the end of the study. Assisted by programmers, the hierarchy is expected to be developed into computer software in the near future to improve construction management.